The Role and Function of a Higher Degree Program for Educators : Case Study UUM/IAB Program - Aminudin, Ibrahim (1996)
Training and development has become one of the important factors in all organizations. Every organization needs workers who have appropriate skills and are always prepared to accept whatever task given. That is why, the role of training and development has become very important in producing skilled and talented workers.The purpose of this study is to explore and investigate the interest and experience among educators in undergoing training. In this study, the focus was on educators who followed the UUM/IAB Twinning program. The sample comprised of 99 participants from Cohorts One and Two. The main objective of this study is to investigate the benefits derived by students from this twinning program and the relevancy between the management courses offered and the career objectives among students. Besides that, the main objective of this study is to investigate whether the UUM/IAB twinning program can help students in their professional development or the other way round. In order to achieve the objectives of the study, the areas of study are divided into seven areas: (a) Students' feeling about going back to studies; (b) Students' career objectives; (c) Employment and job placement; (d) Students' perception toward the management of the UUM/IAB twinning program; (e) Level of relevancy and interest toward each of the courses offered; (f) Students' perception toward study groups; (g) Preparation of research